Ultrasonic Deep-Plane Neck Lift - Gentile, Richard D. (Facial Plastic Surgery, 2023)
Ultrasonic deep-plane neck lift is a new approach for addressing both the subsuperficial musculoaponeurotic system and subplatysmal soft tissues during facial rejuvenation procedures. This innovative surgical approach utilizes 2.2, 2.9, and 3.7 stainless steel probes that are powered by high-frequency ultrasound. Using high-frequency ultrasound in the subcutaneous spaces has been accomplished for the past 20 years with a very suitable safety profile. In this technique, emulsification of the fat layer in both the superficial and deep planes is accomplished with tumescence of the soft tissues in the same fashion as subcutaneous liposuction. In ultrasonic deep-plane neck lift, the superficial and deep layers of fat are targeted for emulsification, and this creates a loosening of these spaces for lifting and repositioning. The procedure facilitates more accurate surgery, because the tissue effects include hemostasis and scalpel- and scissor-free undermining due to the emulsification of the fat layers of the face and neck. The other advantages of ultrasound-assisted facial contouring and rejuvenation include treatment of hard-to-treat areas like the perioral region and distal neck, which can be rapidly and safely undermined utilizing this technology. The third component of ultrasound- and energy-based facial rejuvenation surgery is the long-term remodeling and tightening that occurs beginning approximately 8 weeks after the procedure. When many conventional facelifts are beginning to fall at 3 to 4 months postoperatively, the energy-based facelifts are still tightening and this remodeling continues for up to a year after the procedure. Combining technology with conventional facelift procedures is a new approach to facial rejuvenation and is the result of 15 years of research and cooperation with the aesthetic device industry. The result of this merger of technology with conventional surgery is TESLA Facelifting, the facelift of the future.
Keywords: TESLA Facelift; FaceTite; Renuvion; high-definition facelift; VASER